Elementary school compliance with a state recess minimum requirement by racial and geographic factors: a cross-sectional study - Erin K. Howie; Samantha M. Harden; Daheia J. Barr-Anderson; Christopher R. Long (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background Recess is a part of school-based physical activity promotion offered worldwide with equitable recess access a social justice issue. From a policy perspective, in the U.S. few states currently require elementary school recess and little is known about its implementation. The purpose of this study was to determine the current implementation of one state system as a case study to investigate minimum recess requirement and to compare the implementation between school geographic and racial factors. Methods A cross-sectional, observational study of the implementation of one state’s minimum daily recess requirement of 40-minutes recess was conducted during the 2023–2024 academic year. A school audit of provided recess time was conducted of all public elementary schools in Arkansas through an online search of bell schedules, a survey sent to principals and physical education teachers, and phone call surveys to school offices. Key demographic and geographic features of the schools included enrollment data (e.g., race, grade, and % Free-and-Reduced Lunch composition), rurality, and region. Results Recess information was obtained from 384 (73%) of 526 eligible schools with an average student enrollment of 398 students (SD 154), 19.8% (SD 27.9) Black student enrollment, and 63.8% (SD 20.0%) students receiving free-and-reduced lunch. 306 (85.5%) schools met recess requirements. There were no differences in meeting recess requirements by rurality. Of schools with higher Black student enrollment (≥ 25% Black enrollment), 75.3% met recess requirements compared to 89.5% in schools with lower Black enrollment (< 25% Black enrollment, OR 0.36, 95%CI: 0.16, 0.78, p =.010). There were differences in survey-reported available playground spaces and equipment between by meeting recess requirements and Black student enrollment (p <.05). Conclusions Schools in a state with a 40-minute daily recess requirement reported high compliance with the state policy. However, students in schools with higher Black student enrollment were less likely to meet the 40-minute recess requirement, and thus strategies are needed to ensure all students have access to recess opportunities. Ensuring equal access to recess through wide-reaching place-based and policy-based strategies may be a step in reducing health and education disparities, especially among populations where disparities are greatest.